Superwetting surfaces for filtration separation of high-viscosity raw petroleum/water mixtures. Issue 27 (29th June 2022) - Jiang, Xian; Yang, Fuchao; Guo, Zhiguang
Abstract : We provide an overview of the filtration separation of crude oil/water mixtures, and future opportunities and challenges are presented. Abstract : The petroleum industry produces a large amount of crude oil-contaminated water during the production process. Removing oil and grease components from crude oil/water mixtures is an urgent problem and a great challenge. Filtration separation technology is considered the superior method for oil–water separation because of its broad applicability, simple operation, and low cost. However, crude oil is extremely viscous and complex in composition, and the separation performance of conventional filtration separation materials is not satisfactory to improve the separation performance of crude oil/water mixtures. Recently, various advanced filtration and separation materials have been developed, such as self-cleaning filter membranes and materials resistant to crude oil contamination. This review begins from describing the context of crude oil as well as crude oil/water mixtures. Then, for the design of more complex crude oil/water mixture separation materials, nature-inspired oil–water separation materials are also investigated to provide some ideas. The basic surface wetting theories are also described in detail. In addition, the most advanced materials for the separation of crude oil/water mixtures based on filtration separation technology are presented, including their separation strategies, mechanisms, preparation methods, and separation capabilities. Lastly, conclusions and difficulties in separating high-viscosity raw petroleum/water mixtures are reviewed.